Activation of MEK1/2/Nrf-2 Signaling Pathway by Epstein-Barr Virus-Latent Membrane Protein 1 Enhances Autophagy and Cisplatin Resistance in T-Cell Lymphoma - Xintao Jia; Qiuyu He; Mei Zeng; Yuhua Chen; Yan Liu (Analytical Cellular Pathology)
Epstein-Barr virus-latent membrane protein 1 (EBV-LMP1) was associated with lymphoma, but its specific mechanism is still controversial. The study is aimed at studying the regulation of lymphoma resistance by EBV-LMP1 through the MEK1/2/Nrf-2 signaling pathway. First, LMP1 was knocked down in EBV-positive SNK-6 cells and overexpressed in EBV-negative KHYG-1 cells. First, we found that overexpression of LMP1 significantly promoted the resistance of KHYG-1 cells to cisplatin (DDP), which was related to increased autophagy in the cells. In contrast, knockdown of LMP1 expression in SNK-6 cells promoted cellular sensitivity to DDP and reduced the autophagy of cells after DDP treatment. Moreover, specific inhibition of autophagy in KHYG-1 cells significantly attenuated the resistance to DDP caused by overexpression of LMP1, but treatment with rapamycin in SNK-6 cells significantly promoted the autophagy in the cells. Subsequently, overexpression of LMP1 promoted the activation of the MEK1/2-Nrf2 pathway in KYHG-1 cells, whereas knockdown of LMP1 in SNK-6 cells inhibited the activation of the MEK1/2-Nrf2 pathway. Inhibition of MEK1/2/Nrf-2 blocked the promoting effects of LMP1 on lymphoma cell resistance. In conclusion, EBV-LMP1 promotes cell autophagy after DDP treatment by activating the MEK1/2/Nrf-2 signaling pathway in lymphoma cells, thus, enhancing the resistance of lymphoma cells to DDP.